All in the Family? An Exploratory Study of Family Member Advisors and Firm Performance. (September 2015) - Naldi, Lucia; Chirico, Francesco; Kellermanns, Franz W.; Campopiano, Giovanna
This exploratory study investigates the relationship between family members serving in an advising capacity and family firm performance. Integrating the stewardship and agency perspectives, we predict an inverted U-shaped relationship between the number of family advisors and family firm performance. We argue that the generation in control moderates this relationship such that family member advisors have a positive relationship with performance in first-generation family firms and an inverted U-shaped relationship with performance in later-generation family firms. Our empirical analysis on a sample of 128 Swedish family firms confirms our hypotheses. In the concluding section, we discuss results, contributions and future research directions.